Bridging Cultural and Linguistic Gaps with AI-Based Knowledge Management: A Solution for Language and Cultural Barriers at PT. STI - Christian Susanto; Achmad Fajar Hendarman (Green Publisher Indonesia, 2025)
In today’s globalized economy, multinational corporations like PT. STI face significant challenges in enabling seamless knowledge sharing across culturally and linguistically diverse teams. This study proposes an Artificial Intelligence-based Knowledge Management (KM) system to address language and cultural barriers causing operational inefficiencies such as project delays and reduced productivity at PT. STI. Using a mixed-methods approach, the research applies the Asian Productivity Organization (APO) KM Framework to evaluate the company’s KM maturity, the Analytical Hierarchy Process (AHP) to prioritize AI features, and the Technology Acceptance Model (TAM) to assess employee perceptions of the system's usefulness and ease of use. Quantitative data from APO KM and AHP surveys were complemented by qualitative insights from semi-structured interviews with key personnel. The APO KM assessment shows PT. STI at the